Mold repair welding materials and molds
A mold repair welding material with optimized chemical composition addresses blowhole resistance and hardness issues, ensuring effective repair and extended mold life, particularly in nitrided molds.
Patent Information
- Application Number
- JP2021034688
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-04
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2041-03-04
AI Technical Summary
Existing mold repair welding materials face challenges in providing both adequate blowhole resistance and hardness, particularly when used to repair molds with a nitride layer, leading to reduced die life.
A mold repair welding material with specific chemical composition, including C: 0.15-0.30%, Si: 0.20-0.50%, Mn: 0.20-0.50%, Cr: 6.0-12.0%, Mo: 0.45-1.50%, V: 0.05-0.65%, O: 0.05% or less, N: 0.10% or less, P: 0.05% or less, S: 0.05% or less, and other elements within specified ranges, optimized to enhance blowhole resistance and hardness.
The material effectively suppresses blowholes and maintains appropriate hardness, extending the life of molds by preventing wear and cracking, especially in nitrided molds with a surface nitrogen layer.
Smart Images

Figure 0007655009000003 
Figure 0007655009000001 
Figure 0007655009000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a mold repair welding material used for the weld repair of a mold, and a mold which has been weld repaired using the same. [Background technology]
[0002] Conventionally, hot die tool steels such as JIS SKD61 are widely used for die casting dies and hot forging dies. When cracks or wear due to heat checking occur in these dies, the damaged parts are repaired by welding using a welding rod or welding wire in order to improve the life of the dies. For this reason, die repair materials have been developed with a focus on toughness, hardness, high-temperature hardness, thermal conductivity, heat checking resistance, and softening resistance, taking into account the life of the dies after repair (see, for example, Patent Document 1 below).
[0003] Meanwhile, in die casting dies and hot forging dies, gas soft nitriding or salt bath nitriding is sometimes performed to form a hard nitride layer on the surface of the die in order to improve the die life. When such dies are repaired using the above repair materials, blowholes (welding defects) caused by the nitride layer formed on the die surface are generated, which causes a problem of significantly shortening the die life. As shown in the following Patent Document 2, a welding material that takes into consideration blowhole resistance has been developed, but the hardness of the repair weld is low and it is not suitable as a material for mold repair. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-24053 A [Patent Document 2] JP 2015-110240 A Summary of the Invention [Problem to be solved by the invention]
[0005] In view of the above circumstances, an object of the present invention is to provide a die repair welding material which is excellent in blowhole resistance and can provide a welded portion with appropriate hardness, and a die which has been welded and repaired using the same. [Means for solving the problem]
[0006] Claim 1 relates to a mold repair welding material, and is characterized in that it contains, by mass%, C: 0.15-0.30%, Si: 0.20-0.50%, Mn: 0.20-0.50%, Cr: 6.0-12.0%, Mo: 0.45-1.50%, V: 0.05-0.65%, O: 0.05% or less, N: 0.10% or less, P: 0.05% or less, S: 0.05% or less, with the remainder being Fe and unavoidable impurities.
[0007] In addition, the mold repair welding material may contain the following components as unavoidable impurities within the following ranges. H≦0.0002%, Sn≦0.1%, Pb≦0.01%, Bi≦0.01%, Zn≦0.01%, Ga≦0.01%, Ge≦0.01%, Se≦0.01%, In≦0.01%, Sb≦0.01%, Te≦0.01%, Ag≦0.01%, Mg≦0.005%, Ca≦0.005%, etc.
[0008] Claim 2 is characterized in that in claim 1, it further contains, by mass %, Al: 0.001 to 0.700%.
[0009] Claim 3 is characterized in that in any one of claims 1 and 2, it further contains, by mass%, one or more of Ti, Nb, Zr, Ta, Y and Hf in a total amount of 0.40% or less.
[0010] A fourth aspect of the present invention is characterized in that, in any one of the first to third aspects, the steel further contains, by mass %, one or two of Ni and Cu in a total amount of 1.00% or less.
[0011] Claim 5 is characterized in that in any one of claims 1 to 4, it further contains, by mass %, any one or more of Co: 1.00% or less, B: 0.01% or less, and W: 1.50% or less.
[0012] Claim 6 relates to a mold, which is a nitrided mold having a surface layer with a nitrogen concentration of 0.5 mass% or more, and is characterized in that it has been welded and repaired with the mold repair welding material described in any one of claims 1 to 5.
[0013] The die repair welding material of the present invention as described above has an increased Cr content, focusing on the fact that the addition of Cr is effective in improving blowhole resistance. However, an increase in the Cr content leads to an increase in the amount of retained austenite, which reduces the hardness of the welded part. Therefore, in the present invention, the Cr content is increased while optimizing the lower limit of the C content and the amount of added carbide-forming elements to ensure the amount of C in the matrix required for appropriate hardness. The die repair welding material of the present invention not only improves blowhole resistance, but also provides the welded part with an appropriate hardness that can suppress the occurrence of wear and cracking during use of the die, thereby extending the life of the die. The mold repair welding material of the present invention is suitable as a repair welding material to be used for molds made of hot work mold tool steel represented by general-purpose steel JIS SKD61, in particular as a repair welding material to be used for molds having a nitride layer on the surface.
[0014] Next, the reasons for adding and limiting each chemical component in the present invention will be explained below. C: 0.15-0.30% C is an important element that determines the hardness of the welded portion, and if it is less than 0.15%, the hardness will be insufficient. Conversely, if it exceeds 0.30%, the hardness will be too hard, increasing the risk of cracking after welding. Therefore, in the present invention, C is contained within the range of 0.15 to 0.30%, and a more preferable range is 0.17 to 0.30%.
[0015] Silicon: 0.20 to 0.50% Si is an element that is useful for increasing softening resistance. When used for welding repair of hot forging dies, if the softening resistance is low, the welded part will soften during forging. If the welded part softens, heat checks will easily occur there. Therefore, in the present invention, the Si content is 0.20% or more to increase the softening resistance. On the other hand, if the Si content is more than 0.50%, the thermal conductivity decreases and heat checks will easily occur. Therefore, in the present invention, the Si content is within the range of 0.20 to 0.50%.
[0016] Mn: 0.20~0.50% If the Mn content is less than 0.20%, the hardness is insufficient, and if the Mn content is reduced to less than 0.20%, the composition of the raw materials must be considered, which increases the manufacturing cost. On the other hand, if the Mn content exceeds 0.50%, the thermal conductivity decreases. Therefore, in the present invention, the Mn content is set within the range of 0.20 to 0.50%.
[0017] Cr: 6.0~12.0% Cr is an essential element for improving blowhole resistance, as it is highly effective in suppressing nitrogen gasification and promoting solid solution. In order to improve blowhole resistance, it is necessary to add 6.0% or more. However, excessive addition increases the amount of retained austenite, reducing the hardness of the welded portion. Therefore, in the present invention, Cr is contained within the range of 6.0 to 12.0%. A more preferable range is 6.8 to 12.0%.
[0018] Mo: 0.45-1.50% Mo is an element useful for improving softening resistance. However, if it is less than 0.45%, the effect on softening resistance is small, so in the present invention, Mo is contained in an amount of 0.45% or more. Also, if it is added in excess of 1.50%, the melting cost increases. Therefore, in the present invention, Mo is contained in the range of 0.45 to 1.50%.
[0019] V: 0.05~0.65% V plays a role in preventing grain coarsening due to VC precipitation (pinning effect). If it is less than 0.05%, the amount of VC precipitation is small and it is difficult to obtain the pinning effect. Therefore, in the present invention, V is contained in an amount of 0.05% or more. Also, the more V content there is, the more V carbides are increased and high-temperature strength is improved. However, if it is contained in an amount of more than 0.65%, C that contributes to hardness is consumed to form coarse carbides, which reduces the hardness and toughness of the weld. Therefore, in the present invention, V is contained in the range of 0.05 to 0.65%.
[0020] O: 0.05% or less If the O content exceeds 0.05%, the amount of coarse oxides increases, which reduces the toughness of the welded portion, and therefore, in the present invention, the O content is limited to 0.05% or less.
[0021] N: 0.10% or less N promotes the formation of blowholes when the content is more than 0.10%, therefore, in the present invention, the N content is limited to 0.10% or less.
[0022] P: 0.05% or less, S: 0.05% or less P and S are elements that promote weld cracking, and therefore, in the present invention, the P and S contents are each limited to 0.05% or less.
[0023] Al: 0.001 to 0.700% Al is an element that easily forms nitrides and is useful for improving blowhole resistance, and can be added as necessary. When Al is added at 0.001% or more, nitrogen dissolved in the molten metal during welding is trapped as nitrides, suppressing the generation of blowholes. On the other hand, when it is added at more than 0.700%, it causes an increase in melting costs and a decrease in thermal conductivity. Therefore, in the present invention, the Al content is set to the range of 0.001 to 0.700%.
[0024] One or more of Ti, Nb, Zr, Ta, Y and Hf: 0.40% or less in total Ti, Nb, Zr, Ta, Y and Hf are elements that combine with carbon or nitrogen to form carbides, nitrides or carbonitrides, and contribute to suppressing the coarsening of crystal grains, and can be contained as necessary. These elements form precipitates, act as pinning particles for austenite crystal grains, and suppress the coarsening of crystal grains. They also form fine grains, thereby increasing toughness. However, if they are contained in excess of 0.40%, C, which contributes to hardness, is consumed to form coarse carbides, resulting in a decrease in hardness and toughness. Therefore, in the present invention, the total content of these elements is limited to 0.40% or less.
[0025] Ni, Cu type 1 or type 2: Total 1.00% or less The addition of Ni and Cu delays the formation of pearlite and improves hardenability. However, adding more than necessary increases costs. It also promotes the formation of blowholes. In the present invention, either Ni or Cu alone can be contained, or both can be contained, but the total content of Ni and Cu is limited to 1.00% or less.
[0026] Co: 1.00% or less, W: 1.50% or less Adding Co and W can increase high temperature strength. However, adding more than necessary increases costs and reduces thermal conductivity. Therefore, the Co content is limited to 1.0% or less and the W content is limited to 1.5% or less.
[0027] B: 0.01% or less B segregates at grain boundaries to strengthen them, and also improves toughness by finely dispersing grain boundary carbides. However, since excessive B content can cause weld cracks, the B content is limited to 0.01% or less. [Brief description of the drawings]
[0028] [Figure 1] FIG. 1 is an explanatory diagram for the evaluation of blowhole resistance characteristics. EXAMPLES
[0029] Next, examples of the present invention will be described in detail. Test pieces were prepared using the welding rods of the examples and comparative examples (total of 39 types) shown in Tables 1 and 2 below, and various evaluations were performed.
[0030] 1. Preparation of Test Specimens Two types of plates made of JIS SKD61 with dimensions of 50 × 150 × 13.5 mm were prepared. One is a plate that has been subjected to salt bath nitriding treatment (Prevents Scoring and Scuffing (PS) treatment) by Daido DM Solution Co., Ltd. at 550℃ for 10 hours to form a nitride layer with a nitrogen concentration of 0.5 mass% or more on the surface. The other is a plate that has not been subjected to PS treatment and has no nitride layer formed.
[0031] For plates with a nitrided layer, only one layer was TIG welded using welding rods (Φ2.0mm×1000mm) with the various chemical compositions shown in Tables 1 and 2. For plates without a nitrided layer, five layers were overlaid by TIG welding using welding rods (Φ2.0mm×1000mm) with the various chemical compositions shown in Tables 1 and 2. The weld length was 100mm for each.
[0032] The diameter of the welding material is preferably 0.2 to 3.5 mm. If the diameter is smaller than 0.2 mm, more heat is applied to the base material during welding, causing the base material to melt in large quantities, which leads to the weld being harder than necessary. On the other hand, if the diameter is larger than 3.5 mm, the heat during welding is absorbed by the welding material and is not applied sufficiently to the base material, which causes insufficient fusion.
[0033] The welding conditions were as follows: Ar was used as the shielding gas, the welding rod was inserted into an arc, heated, and melted to perform welding. The welding current was 120 A, and the welding speed was 5 cm / min.
[0034] 2. Evaluation The obtained welded test pieces (plates) were used to evaluate the blowhole resistance property and the hardness of the welded part.
[0035] <Evaluation of blowhole resistance properties> Ten cross sections of the weld overlay of the plate on which the nitride layer was formed were cut out, and polished and corroded so that the boundary between the weld overlay and the base material could be distinguished. Then, as shown in Fig. 1, the cross sections were observed and microscopic images were taken using an optical microscope, and the total area of blowholes confirmed in the weld overlay was calculated using Win ROOF (Mitani Shoji Co., Ltd.). The area of the blowholes was then calculated by dividing the area by the number of fields of view (10 in this case). The magnification during observation was 50x. When the entire weld overlay could not be captured in one microscopic image, two or more images were taken and evaluated. The evaluation criteria were as follows: ○: Blowhole area (mm 2 ) is 0.025 or less △: Blowhole area (mm 2 ) is over 0.025 to 0.030 ×: Blowhole area (mm 2 ) is over 0.030 These results are shown in Tables 1 and 2.
[0036] <Hardness evaluation> A cross section of the weld overlay of a plate without a nitrided layer was cut out at one location, and polished and corroded so that the boundaries of each weld overlay could be distinguished. After confirming the position of the fifth weld overlay, it was polished again. Then, a beaker hardness test (load 300gf) was performed 10 times at the center of the fifth weld overlay, and the hardness (as-welded hardness) was calculated by finding the average value. The evaluation criteria were as follows: ○:HV420~Less than 550 △: HV400~less than 420 ×: Less than HV400 or more than HV550 These results are also shown in Tables 1 and 2.
[0037] [Table 1]
[0038] [Table 2]
[0039] The evaluation results in Tables 1 and 2 reveal the following: Comparative Example 1 is a conventionally known welding material disclosed in the above-mentioned Patent Document 1. In this Comparative Example 1, the hardness of the weld was sufficient, but the Cr content was low and the blowhole resistance property was evaluated as "x".
[0040] Comparative Example 11 is a conventionally known welding material disclosed in the above Patent Document 2. This Comparative Example 11 is a welding material that takes into consideration blowhole resistance, and the blowhole resistance was evaluated as "◯", but sufficient hardness of the weld was not obtained, and the hardness was evaluated as "×".
[0041] In Comparative Example 2, Cr was added in an excessive amount exceeding the range specified in the present invention, and the blowhole resistance was evaluated as "○", but the hardness was evaluated as "×". It is believed that the hardness was reduced due to an increase in retained austenite.
[0042] In Comparative Example 3, Ni was added in an excessive amount exceeding the range specified in the present invention, and the hardness was evaluated as "○", but the blowhole resistance was evaluated as "×". It is believed that Ni inhibited the solid solution of nitrogen, increasing the number of blowholes.
[0043] In Comparative Example 4, the Cr content was less than the range specified in the present invention, and the blowhole resistance was evaluated as "x".
[0044] Comparative Example 5 is an example in which Cu was added in an amount exceeding the range specified in the present invention, and similarly to Comparative Example 3, the blowhole resistance was evaluated as "x". Similarly, the blowhole resistance of Comparative Example 6, in which Ni and Cu were excessively added, was also evaluated as "x".
[0045] In Comparative Example 7, C was less than the range specified in the present invention, and the hardness was evaluated as "x".
[0046] Comparative Example 8 is an example in which Nb, Comparative Example 9 is an example in which V, and Comparative Example 10 is an example in which the total of Zr and Ti were added in excess of the range specified in the present invention. In all of these comparative examples, the hardness was evaluated as "x." It is believed that the hardness was reduced because the amount of coarse carbides increased and the amount of C in the matrix decreased.
[0047] Comparative Example 12 is an example in which C was added in excess of the range specified in the present invention, and the welded portion became too hard, resulting in a hardness evaluation of "x".
[0048] Comparative Example 13 is an example in which N was added in an amount exceeding the range specified in the present invention, and the blowhole resistance property was evaluated as "x".
[0049] In Comparative Example 14, the Mn content was less than the range specified in the present invention, and the hardness was evaluated as "x".
[0050] As described above, in each of the comparative examples, at least either the hardness or the blowhole resistance was evaluated as "x".
[0051] In contrast, in Examples 1 to 25, in which the chemical composition of the welding material (welding rod) is within the range of the present invention, both the hardness and the blowhole resistance were evaluated as "○" or "△", and it is found that these two properties are compatible with each other compared to the conventionally known welding materials (Comparative Example 1 and Comparative Example 11). The welding material of the present invention can effectively suppress the occurrence of blowholes even when used to repair a nitrided mold having a surface layer with a nitrogen concentration of 0.5 mass % or more, and can also provide a repair weld with appropriate hardness.
[0052] Looking more closely at the examples, it is possible to further increase the hardness by adding more C within the range specified in the present invention, and examples in which the C content was 0.17% or more were evaluated as "○" for hardness. Furthermore, by adding more Cr within the range specified in the present invention, the blowhole resistance properties can be further improved, and examples with a Cr content of 6.8% or more were evaluated as having blowhole resistance properties of "O."
[0053] Furthermore, when comparing Example 9 with Example 16, Example 18 with Example 14, etc., it is found that the area of blowholes is smaller in the examples in which Al was added, and that the addition of Al is effective in improving the blowhole resistance characteristics.
[0054] Although the embodiment of the present invention has been described in detail above, the present invention is not limited to this embodiment, and various modifications can be made without departing from the spirit and scope of the present invention.
Claims
1. By mass% C: 0.15-0.30% Si: 0.20-0.50% Mn: 0.20-0.50% Cr:6.0~12.0% Mo: 0.45-1.50% V: 0.05-0.65% O: 0.05% or less N: 0.10% or less P: 0.05% or less S: 0.05% or less and the balance being Fe and unavoidable impurities.
2. In claim 1, in mass % Al: 0.001-0.700% A mold repair welding material further comprising:
3. In any one of claims 1 and 2, One or more of Ti, Nb, Zr, Ta, Y and Hf in total: 0.40% or less A mold repair welding material further comprising:
4. In any one of claims 1 to 3, One or two of Ni and Cu in total: 1.00% or less A mold repair welding material further comprising:
5. In any one of claims 1 to 4, in mass % Co: 1.00% or less B: 0.01% or less W: 1.50% or less 13. A mold repair welding material comprising:
6. A nitrided mold having a surface layer with a nitrogen concentration of 0.5 mass% or more, the mold being welded and repaired with the mold repair welding material according to any one of claims 1 to 5.
Citation Information
Patent Citations
Hot werk mould steel welding material
CN1718353A
Gas shield arc welding wire for high cr ferrite system heat resistant steel
JP2000071093A
Die repair welding material and die repair welding method using the same
JP2011245488A
Welding consumable for austenitic heat-resistant steel and weld metal and welded joint obtained by using the same
JP2015110240A
Steel for mold
JP2015168859A